Plants face the flow in V formation: A study of plant patch alignment in streams. (14th December 2018) - Cornacchia, Loreta; Folkard, Andrew; Davies, Grieg; Grabowski, Robert C.; van de Koppel, Johan; van der Wal, Daphne; Wharton, Geraldene; Puijalon, Sara; Bouma, Tjeerd J.
Abstract: Interactions between biological and physical processes, so‐called bio‐physical feedbacks, are important for landscape evolution. While these feedbacks have been quantified for isolated patches of vegetation in aquatic ecosystems, we still lack knowledge of how the location of one patch affects the occurrence of others. To test for patterns in the spatial distribution of vegetation patches in streams, we first measured the distance between Callitriche platycarpa patches using aerial images. Then, we measured the effects of varying patch separation distance on flow velocity, turbulence, and drag on plants in a field manipulation experiment. Lastly, we investigated whether these patterns of patch alignment developed over time following locations of reduced hydrodynamic forces, using 2‐yr field observations of the temporal patch dynamics of Ranunculus penicillatus in a lowland chalk stream. Our results suggest that vegetation patches in streams organize themselves in V‐like shapes to reduce drag forces, creating an optimal configuration that decreases hydrodynamic forces and may therefore encourage patch growth. Downstream patches are more frequently found at the rear and slightly overlapping the upstream patch, in locations that are partially sheltered by the established upstream vegetation while ensuring exposure to incoming flow (important for nutrient availability). Observations of macrophyte patch dynamics over time indicated that neighboring patches tend to grow in a slightly angled line, producing a spatial pattern resembling the V‐formation in migratory birds. These findings point to the general role of bio‐physical interactions in shaping how organisms align themselves spatially to aerodynamic and hydrodynamic flows at a range of scales.